2017
DOI: 10.1002/ar.23536
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Ameliorating Impacts of Omega‐3 Against Aspartame‐induced Neuronal and Astrocytic Degeneration

Abstract: Aspartame (ASP) is one of the commonest artificial sweetener used all over the world and considered as an extremely risky compound and raises a lot of controversy. Therefore, this study was designed to investigate cellular damage of the anterior horn cells in the spinal cord of albino male rats and the possibility of hindering these changes by using omega-3 (OM3).Thirty seven adult male albino rats were divided into three groups: Control, ASP-treated and ASP + OM3-treated groups. Spinal cord sections were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Thus, by increasing astrocyte abundance via ω3 PUFAs administration, neuroprotection of the eye may be established. A similar effect was recently demonstrated by treating anterior horn cells in the spinal cord of male albino rats with ω3 PUFAs plus aspartame; rats treated with aspartame alone showed a higher rate of cell death and fewer GFAP-positive astrocytes 69. In addition, Zgórzyńska et al showed that the incubation of rat primary astrocytes with DHA and EPA improves the antioxidant defense in astrocytes via an Nrf2-dependent mechanism, determined by the ratio of DHA to EPA incorporated into membrane phospholipids 70.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, by increasing astrocyte abundance via ω3 PUFAs administration, neuroprotection of the eye may be established. A similar effect was recently demonstrated by treating anterior horn cells in the spinal cord of male albino rats with ω3 PUFAs plus aspartame; rats treated with aspartame alone showed a higher rate of cell death and fewer GFAP-positive astrocytes 69. In addition, Zgórzyńska et al showed that the incubation of rat primary astrocytes with DHA and EPA improves the antioxidant defense in astrocytes via an Nrf2-dependent mechanism, determined by the ratio of DHA to EPA incorporated into membrane phospholipids 70.…”
Section: Discussionsupporting
confidence: 77%
“…The failure of the antioxidant mechanisms led to accumulation of free radicals and uncompensated oxidative stress with subsequent accumulation of denatured proteins and dark staining of the degenerated cells. Some authors agreed with this explanation [25,19] .…”
Section: Discussionmentioning
confidence: 91%
“…Although studies of sucralose [22,28] and aspartame [11][12][13]29] reflect potential health risks, these sweeteners are most consumed by Estonian fitness athletes. The situation is similar in Ireland [30] and Italy [31].…”
Section: Discussionmentioning
confidence: 99%